Two‐day assertive‐case‐management educational program for medical personnel to prevent suicide attempts: A multicenter pre–post observational study. Issue 6 (7th April 2020) - Kawashima, Yoshitaka; Yonemoto, Naohiro; Kawanishi, Chiaki; Otsuka, Kotaro; Mimura, Masaru; Otaka, Yasushi; Okamura, Kazuya; Kinoshita, Toshihiko; Shirakawa, Osamu; Yoshimura, Reiji; Eto, Nobuaki; Hashimoto, Satoshi; et al.
Abstract : Aim: Suicide attempters have a high risk of repeated suicide attempts and completed suicide. There is evidence that assertive case management can reduce the incidence of recurrent suicidal behavior among suicide attempters. This study evaluated the effect of an assertive‐case‐management training program. Methods: This multicenter, before‐and‐after study was conducted at 10 centers in Japan. Participants were 274 medical personnel. We used Japanese versions of the Attitudes to Suicide Prevention Scale, the Gatekeeper Self‐Efficacy Scale, the Suicide Intervention Response Inventory (SIRI), and the Attitudes Toward Suicide Questionnaire. We evaluated the effects with one‐sample t ‐tests, and examined prognosis factors with multivariable analysis. Results: There were significant improvements between pre‐training and post‐training in the Attitudes to Suicide Prevention Scale (mean: −3.07, 95% confidence interval [CI]: −3.57 to −2.57, P  < 0.001), the Gatekeeper Self‐Efficacy Scale (mean: 10.40, 95%CI: 9.48 to 11.32, P  < 0.001), SIRI‐1 (appropriate responses; mean: 1.15, 95%CI: 0.89 to 1.42, P  < 0.001), and SIRI‐2 (different to the expert responses; mean: −4.78, 95%CI: −6.18 to −3.38, P  < 0.001). Significant improvements were found on all Attitudes Toward Suicide Questionnaire subscale scores, except Unjustified Behavior. The effect of training was influenced by experience of suicide‐prevention training and experience of working with suicidal patients. Conclusion: The training program (which was developed to implement and disseminate evidence‐based suicide‐prevention measures) improved attitudes, self‐efficacy, and skills for suicide prevention among medical personnel. Specialized suicide‐prevention training and experience with suicidal patients are valuable for enhancing positive attitudes and self‐efficacy; furthermore, age and clinical experience alone are insufficient for these purposes.